Performance of Weaned Boer Cross Goats with Supplementation of Hibiscus (Hibiscus rosasinensis L) Leaf Powder - Husandi; Agustina; Indah, Andi Sukma (Program Studi Peternakan, Fakultas Pertanian, Sains dan Kesehatan, Universitas Timor, 2025)
This study aimed to determine the performance of weaned Cross Boer goats by feeding supplementation of Hibiscus leaves. The performance of weaned Cross Boer goats at different body weights was evaluated based on feed intake, daily weight gain, and feed conversion ratio. The research was conducted at JK Community as a goat breeding commodity for cross-boer goats. This study used an experimental method using a Randomized Group Design (RGD) with 3 treatments and 4 replicates with 12 sample units of weaned Cross Boer goats. The treatment feed consisted of P0 = Basal feed without Hibiscus leaf supplementation, P1 = Basal feed + 2% Hibiscus leaf supplementation, and P2 = Basal feed + 4% Hibiscus leaf supplementation. Weaned Cross Boer goats as test material have an average age of 3 months of male and female sex with an average body weight at the beginning of maintenance of 8.2 - 9.7 kg. The study was conducted with a maintenance time of 30 days. The results showed that feed intake and conversion of weaned male Cross Boer goats significantly affected the treatment but did not show any effect on body weight gain.